2021
DOI: 10.1002/advs.202100914
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic NEAT1 Suppresses AML Stem Cell Self‐Renewal and Leukemogenesis through Inactivation of Wnt Signaling

Abstract: As an essential component of paraspeckles, nuclear paraspeckle assembly transcript 1 (NEAT1) localizes in the nucleus, promoting progression of various malignant solid tumors. Herein, an adverse effect of NEAT1 is reported, showing that the short isoform, NEAT1_1 suppresses acute myeloid leukemia (AML) development. NEAT1_1 is downregulated in leukemia stem cells (LSCs) and its decreased expression correlates with recurrence in AML patients. It is demonstrated that NEAT1_1 suppresses leukemogenesis and LSC func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…It has been reported that Lnc NEAT1 mediated by exosomes can facilitate endometrial cancer progression [ 18 ]. Recent evidence indicates that Lnc NEAT1 regulates stem cell function [ 19 , 20 ]. Nevertheless, the roles of Lnc NEAT1 in EPC function and skin flap survival remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Lnc NEAT1 mediated by exosomes can facilitate endometrial cancer progression [ 18 ]. Recent evidence indicates that Lnc NEAT1 regulates stem cell function [ 19 , 20 ]. Nevertheless, the roles of Lnc NEAT1 in EPC function and skin flap survival remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Is the role of Neat1 exclusively nuclear in the paraspeckle, or is it exported to the cytoplasm with the IRESome complex? Several observations argue for the presence of Neat1 in the cytoplasm: our FISH experiments clearly identify the Neat1-2 isoform in the cytoplasm (Fig.1, figure supplement 2), while a recent report shows that Neat1-1 isoform is released from nucleus to cytoplasm where it suppresses the Wnt signaling in leukemia stem cells and acts as a tumor suppressor in acute myeloid leukemia (Yan et al, 2021). Neat1-2 isoform has been detected in the cytoplasm of hematopoietic cells by other authors.…”
Section: Discussionmentioning
confidence: 57%
“…The Wnt/ β-catenin pathway is one of the significant signaling pathways involved in stem cell self-renewal. The positive effect of the Wnt/β-catenin pathway on CSC self-renewal has been reported in various cancers [ 90 , 91 ], such as liver cancer [ 90 ], breast cancer [ 92 ], colorectal cancer [ 93 ], and acute myelogenous leukemia [ 94 , 95 ]. Wnt ligands can combine with their receptors Frizzled receptors (Fz) and co-receptors low-density lipoprotein receptor-related protein 5 (LRP5)/6, phosphorylating the cytoplasmic domain of LRP and then recruiting the scaffolding protein Disheveled (Dvl) to disassemble the destruction complex.…”
Section: Csc Self-renewal and Lipid Raftmentioning
confidence: 99%